REKONSTRUKSI BIDANG GELINCIR LONGSOR DENGAN METODE GEOLISTRIK DI KAWASAN TAMAN NASIONAL TAIPINGSHAN, PROPINSI YILAN, TAIWAN - Zamroni, Akhmad (KURVATEK, 2019)
Taipingshan landslide occurred by Typhoon Saola in 2012. Rainfall recorded in that event occurred was over 1800 mm during three days. Additionally, geological factors such as weathered and erosion materials are also factors that give risk occur landslide. Geoelectrical resistivity is a geophysical method that uses an electrical current into the rock to get resistivity value. The function of geoelectrical resistivity is to determine materials in subsurface based on the resistivity value, which is done by measuring materials on the ground surface. The kinds of landslide material in this area is only one type of rock, it is slate. Differences of resistivity values (some colors in 2D resistivity image), due to several factors, such as weathered and fresh rock, fracture zones in the rock, and rock contacts with water. According to drilling data, 2D resistivity image, and geological map in Taipingshan, reconstruction of the subsurface profile was made to know the depth of potential mass wasting. The kinds of materials derived are colluvium at a depth of 0-10 m, weathered rock (slate) at a depth of 10-29 m, and bedrock (slate) at a depth of 29-100 m. The position of sliding surface was located between the weathered rock (slate) and bedrock (slate) at a depth of around 29 m. The sliding surface is obtained from two materials adjacent that has different contrast of resistivity value. So it is easily moving and eroded in steep slope and when heavy rainfall occurs. So that the thickness of potential mass wasting was around 29 m.